Phytochemicals and Monensin in Dairy Cows: Impact on Productive Performance and Ruminal Fermentation Profile - Lucas Gonzalez-Chappe; Maria A. Bruni; Aline C. Dall-Orsoletta; Pablo Chilibroste; Ana Meikle; Maria L. Adrien; Alberto Casal; Juan P. Damián; Hugo Naya; Marisela Arturo-Schaan; Diego A. Mattiauda (Animals)
Phytochemicals are a potential alternative to antibiotic growth promoters. This study evaluated the effects of phytochemicals (curcuminoids, trans-cinnamaldehyde, and piperine) and monensin on performance and ruminal fermentation during the transition period in grazing dairy cows. In a complete randomized design, 60 Holstein cows (36 multiparous, 24 primiparous; 9 fistulated) were assigned to (1) control (CTL), (2) monensin (MON, 0.30 g/cow/day), or (3) phytochemicals (PHY, 50 g/cow/day) treatment from 30 days prepartum to 60 days postpartum. Prepartum, cows received a total mixed ration (TMR); postpartum, they grazed between a.m. and p.m. milking and were supplemented with TMR. Ruminal fermentation was evaluated at −7, 30, and 60 days postpartum. Prepartum dry matter intake was lower in MON primiparous cows than in CTL and PHY. Additives increased milk yield and lactose percentage in primiparous cows. PHY cows had lower acetate, higher propionate, and reduced acetate-to-propionate and ketogenic-to-glucogenic ratios at 60 days postpartum. MON reduced prepartum protozoa, while PHY increased prepartum branched-chain volatile fatty acids (BCVFAs). Both additives decreased BCVFA and protozoa postpartum. Additives reduced ammonia at 30 days, but only PHY persisted at 60 days. MON and PHY improved primiparous performance, enhanced ruminal fermentation, and promoted glucogenic fermentation while reducing ammonia and protozoa.